Bloodstream infection in children. - See, L.L.C. (Lippincott, Williams & Wilkins, 2005)
A BSI is the presence of a pathogen in the blood. Its clinical significance should be determined by the presence of the host response as defined by the modified criteria for systemic inflammatory response syndrome SIRS in children or a clinically recognizable syndrome. Definitions of BSI for the purposes of sepsis trials may differ from those for epidemiologic or surveillance studies.